Analysis of The Effectiveness and Learning Activity of Students Through Online Physics Learning During the Covid-19 Pandemic - Hutauruk, Renni Verawati; Sinon, Iriwi L.S.; Sebayang, Sri Rosepda Br (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2023)
This studed aims to analyze the effectiveness and activeness of students' learning through online physics learning during in the Covid-19 pandemic at SMA Negeri 2 Manokwari. The research method used is the survey method using a questionnaire. The sampling technique is using purposive sampling with a sample of 90 students. The instrument used is an effectiveness questionnaire as many as 16 statements and a learning activity questionnaire as many as 15 statements with data analysis techniques using the Rasch Model with the help of the Winstep application. The results of the analysis show that for the effectiveness of learning the Crombach Alpha value is 0.53, while using the Wright map the distribution of respondents generally gathers between logit SD (+0.00) to logit SD (+2.00) it means that many students are interested in taking physics lessons online and consider it good or effective. Meanwhile, for active learning, the value of Alpha Crombach is 0.64, also using Wright's map the distribution of respondents generally gathered between logit SD (+0.00) to logit SD (+8.00) and above logit SD (-0.80) this means that many students are active in participating in physics learning online and considers the level of active learning is high. This shows that online physics learning at SMA Negeri 2 Manokwari can be said to be good and the level of student activity is high.